Impact of Integrated Village Development Project (IVDP) on Income Consumption and Employment in Tribal Area of Southern Rajasthan - Rajesh Kumar Godara, D.C. Panth , S.S. Burark, (Indian Journal of Extension Education, 2022)
The study has examined the impact of IVDP in southern Rajasthan and assessed the employment generated and changes in income and consumption through IVDP. The annual increase in income of beneficiary families over and above the income of non-beneficiary families varied from Rs. 4259 (medium farmers) to Rs. 4595 (marginal farmers). Percentage increase in net annual income was maximum (25.05 %) in marginal beneficiary farmers followed by small (20.18 %) and medium farmers (15.58 %). In marginal and small farmers the percentage increase in net annual income was maximum in agriculture followed by hiring out of labour and livestock while in medium farmers the percentage increase in net annual income was maximum in agriculture followed by livestock and hiring out of labour. The per year increase in consumption expenditure was Rs.3487 in marginal farmers, Rs.2878 in small farmers and Rs.1953 in medium farmers. The total increase in consumption expenditure over and above the total consumption expenditure of non-beneficiary families varied from 7.47 per cent on medium farmers to 19.20 per cent on marginal farmers. The increased consumption expenditure over increased net income varied from 45.85 per cent (medium farmers) to 75.88 per cent (marginal farmers). The saving (difference) from the increased income varied from Rs. 1108 (marginal farmers) to Rs.2306 (medium farmers). Consumption expenditure on clothing, health, recreation and other items increased with increase in size-groups. Consumption expenditure on food and education decreased with increase in size-groups. The absolute increase in employment in marginal, small and medium beneficiary farmers over non-beneficiary farmer families were 30, 27 and 17 mandays per year, which was 10.38 per cent, 7.6 per cent and 3.65 per cent, respectively as a result of IVDP assistance.